Extraction of phenolic compounds from earthworms Lumbricus rubellus and Eudrilus eugeniae (Authority) and evaluation of their antioxidant activities for cosmeceutical use - Aldarraji, Qasim Mohammed Matrood (2013)
Synthetic materials used in cosmetics products have adverse effects on the skin causing skin irritation. Natural bioactive compounds have no adverse effects on the skin or any other parts of the body. Cosmeceuticals are materials having natural bioactive compounds that have medicinal benefits. Unlike drugs, Cosmeceuticals do not have any adverse biological effects on the living tissues. The objectives of this study were to extract the phenolic compounds present in the earthworm paste (EP) of red worm (Lumbricus rubellus) and African night crawler (Eudrilus eugeniae) and evaluation its antioxidant activity for Cosmeceutical use. The Folin-Ciocalteu procedure was used to quantify the phenolic compounds. Identification of the phenolic compounds in the earthworm paste was achieved by using highperformance liquid chromatography (HPLC), followed by confirmation of compounds using liquid chromatography mass spectroscopy (LC/MS). Tow types of solvent materials were used in the experiment: methanol and ethanol with different concentration levels 80% and 75%. Type of solvent used at different concentration levels had no effects on the total phenolic contents of the earthworm paste. In this study, the earthworm paste from the red worm extract yielded higher amounts of phenolic compounds than that of the African night crawler extract. HPLC analysis of the phenolic compounds revealed the presence of phenolic acids, cinnamic and benzoic acid derivatives, which were measured at 270, 280, 290, 300 and 325 nm. These compounds included gallic, chlorogenic, salicylic, caffeic, syringic and pcoumaric acids. The red worm extract had more phenolic acids than that of the African night crawler extract. LC/MS confirmation showed two compounds in the methanolic extract of the earthworm paste of the African night crawler. These compounds were sinapic and caffeic acids. In the methanolic extract of the earthworm paste of the red worm, four phenolic acids were confirmed according to their molecular weight. The compounds were syringic, p- coumaric, gallic and ferulic acids. The compounds identified were phenolic acids, which showed significant antioxidant activity. The antioxidant activity of each extract was assessed using the DPPH assay. All the extracts showed a strong antioxidant activity. The 75% methanolic extract of the earthworm paste of the red worm exhibited stronger antioxidant activity than that of 80% methanol and 80% ethanol. In contrast, 80% methanolic extract of the earthworm paste of the African night crawler revealed the strongest antioxidant activity. Earthworm extract of African night crawler revealed a stronger antioxidant activity than that of the red worm extract. In conclusion,The results shown that earthworms paste had notable amounts of phenolic compounds with strong antioxidant activity.